2021
DOI: 10.1155/2021/6663696
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Dissolved Oxygen Transportation through a Coupled SWE and Streeter–Phelps Model

Abstract: Dissolved oxygen (DO) reflects the self-purification ability of a water body and is also an important indicator for quantifying the water quality. The morphological changes in the cross sections of river channels will affect the hydraulic conditions, and the distribution of pollutants and DO may also be affected, possibly resulting in local oxygen deficits and pollution. To effectively predict the water quality, a coupled model is introduced in this study. The shallow water equation (SWE) is adopted to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…When the river channel is narrowed, the river flow velocity becomes larger and the degree of S DO increases accordingly. Wu and Yu (2021) study also found that abrupt channel expansion would enhance the self‐purification ability of rivers. In summary, the self‐purification capacity of water bodies at the Weihe–Yellow River confluence shows the following spatial distribution pattern: The self‐purification capacity of water bodies on both sides of the river is stronger than that in the middle of the river, the self‐purification capacity of the upper Weihe River is stronger than that of the upper Yellow River, and the self‐purification capacity downstream of the confluence is stronger than that upstream.…”
Section: Resultsmentioning
confidence: 92%
“…When the river channel is narrowed, the river flow velocity becomes larger and the degree of S DO increases accordingly. Wu and Yu (2021) study also found that abrupt channel expansion would enhance the self‐purification ability of rivers. In summary, the self‐purification capacity of water bodies at the Weihe–Yellow River confluence shows the following spatial distribution pattern: The self‐purification capacity of water bodies on both sides of the river is stronger than that in the middle of the river, the self‐purification capacity of the upper Weihe River is stronger than that of the upper Yellow River, and the self‐purification capacity downstream of the confluence is stronger than that upstream.…”
Section: Resultsmentioning
confidence: 92%
“…Where, DO concentrations are an important index for quantifying the water quality (WQ) of water bodies. Moreover, the level of DO reflects the ecological balance in water, decomposition of organic matter and breathing of aquatic ecosystem [2].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, physically based models are used for DO prediction (Radwan et al, 2003;Wu and Yu, 2021). The models generally use advection and dispersion theories to simulate the biological and chemical processes in water for DO prediction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Radwan et al (2003) used Mike11 for modeling DO in river water. Wu and Yu (2021) used a modified version of the Streeter-Phelps model coupled with the shallow water equation model to simulate mass transportation and DO distribution. The studies indicated the need for a large amount of data and computational time to predict DO reliability.…”
Section: Introductionmentioning
confidence: 99%